Isolation and Identificution of Cryptococcus neoformans from some Environmental resources in Najaf covernorate - A. Majbeel, Fatima; S. Majeed, Nabeel (Journal of Kerbala for Agricultural Sciences, 2017)
The aims of the present study were to isolate and identificate of isolation and identificution of Cryptococcus neoformans from some environmental resources in Najaf covernor associated with fungal infection .C.neoformans represents one of the isolated fungi from environmental resources samples, which may cause many serious problems to human and in immunocompromised patients inparticular. Laboratory isolation and identification of C. neoformans a total of (150) environmental resources samples are collected from (6) different areas; (100) samples are obtained from pigeon droppings and (50) samples from soil surrounding the Eucalyptus sp. trees and decaying wood were collected, during 2015. The positive results of cultures (112) (74.66%) isolates of C. neoformans were isolated from samples of pigeon droppings and isolates from soil sourrunding the Eucalyptus trees and decaying wood samples. The cultural and biochemical methods were used in Cryptococcus spp. Isolation and identification, besides VITEK2 compact system identification kit and CHROM agar candida medium. Also identification by VITEK 2 compact system, showed two speices C. neoformans (12) samples and C. gattii (3) samples. The best trust level appeared within potentiality rate of 93%, however the other isolates had a fewer potentiality rate reached 85% and this level was accepted . Cryptococcus was identified by conventional tests and yeast which show positive results for the capsule test, urease test, melanin pigment when cultured on methyl dopa culture for a period from 18 – 24 hrs. Then confirmed by VITEK2 compact system identification kit. The results of CHROM agar candida medium test are confirmed the results of the VITEK 2 compact yeast identification system. In this test, the colony color of Cryptococcus spp. on the medium are pink for C. neoformans